2020
DOI: 10.4049/jimmunol.1901321
|View full text |Cite
|
Sign up to set email alerts
|

IL-33–Stimulated Murine Mast Cells Polarize Alternatively Activated Macrophages, Which Suppress T Cells That Mediate Experimental Autoimmune Encephalomyelitis

Abstract: IL-33 is known to promote type 2 immune responses through ST2, a component of the IL-33R complex, expressed primarily on mast cells, Th2 cells, group 2 innate lymphoid cells and regulatory T cells, and to a lesser extent, on NK cells and Th1 cells. Consistent with previous studies, we found that IL-33 polarized alternatively activated macrophages (AAMF) in vivo. However, in vitro stimulation of murine bone marrow-derived or peritoneal macrophages with IL-33 failed to promote arginase activity or expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…Further macrophage-derived pro-inflammatory cytokines with suppressive effects on type 2 immunity include IL-6 and IL-1b [125,126], although mast cell-derived IL-6 has been implicated in AAM activation by upregulating IL4Ra on macrophages [127]. Surprisingly, TNFa has been described to promote anti-helminth immunity [128] despite suppressive effects on AAM differentiation [129].…”
Section: Type 2 Suppressive Effects Of Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…Further macrophage-derived pro-inflammatory cytokines with suppressive effects on type 2 immunity include IL-6 and IL-1b [125,126], although mast cell-derived IL-6 has been implicated in AAM activation by upregulating IL4Ra on macrophages [127]. Surprisingly, TNFa has been described to promote anti-helminth immunity [128] despite suppressive effects on AAM differentiation [129].…”
Section: Type 2 Suppressive Effects Of Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…Leptin mutant ob/ob mice showed decreased percentage of mast cells in inguinal adipose tissue, but did not show mast cell deficiencies in other tissues (76). Several studies have proposed a role for mast cells in polarization of macrophages by secretion of cytokines (77). For example, IL-33 treatment of mast cells causes production of IL-6 and IL-13, which are cytokines known to promote alternatively activated macrophages that suppresses T cell inflammation (77).…”
Section: Mast Cellsmentioning
confidence: 99%
“…Several studies have proposed a role for mast cells in polarization of macrophages by secretion of cytokines (77). For example, IL-33 treatment of mast cells causes production of IL-6 and IL-13, which are cytokines known to promote alternatively activated macrophages that suppresses T cell inflammation (77). One group has investigated the role of leptin in mast cell function and the subsequent effect on macrophages in the context of obesity (43).…”
Section: Mast Cellsmentioning
confidence: 99%
“…Accordingly, AAMF has immunosuppressive and anti-inflammatory effects. Notably, IL-6, another cytokine secreted by MCs, can upregulate the IL-4ra in IL-13R, which further enhances the alternating activation of macrophages [ 136 ]. Besides, in a study of autoimmune diabetes, MCs were found to play a protective role by inducing Foxp3 + Treg cells and reducing tissue inflammation [ 137 ].…”
Section: Regulatory-type Actions Of Mcs In Allergy and Inflammationmentioning
confidence: 99%